Ground state properties of soft core bosons on a two-dimensional honeycomb lattice - Abdul Malek Razali (2012)
We study the ground state properties of interacting bosons on a 2 dimensional honeycomb lattice using SSE QMC simulations with directed loop update. We pay particular attention to the supersolid phase. At maximum occupancy of 2 bosons per site, we observe a ρ = 1/2 solid which undergoes a continuous phase transition to a superfluid. At higher chemical potential, the superfluid condenses at continuous transition into a Mott insulator. There is no supersolid observed. At maximum occupancy of 6 bosons per site, we find a wide but narrow region of ρ <1 supersolid which later melts at continuous transition to a superfluid which later on condenses into a Mott insulator at higher chemical potential